Perinatal education: women's needs - descriptive study - Magdalena S. Richter (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2006)
The needs of women concerning perinatal education were investigated using a descriptive qualitative design. Purposive sampling was used; the women were chosen based on their knowledge of their perinatal education needs. Focus groups were conducted. A semi-structured interview guide was used. The data were analyzed according to Tesch's method which interprets the data in the basic sense of reflecting on the data until a better understanding of what is meant is achieved. Analysis of the data started as soon as the first data was collected and continued through the data collection phase. Guba's model was used to ensure the study's trustworthiness. Three categories emerged from the data: Women's needs concerning the perinatal educator's professional and personal traits, the educational activities and interventions, and the content of the perinatal education. Every contact with women in the perinatal period should be used as an opportunity for further education. Perinatal education must be versatile and tailored to reflect the background of the women recipients. Involvement of the partner, father of the baby or significant other in the perinatal education process is essential. Create an environment that makes the women and her significant other more comfortable to ask questions. Recognize that some women are more vulnerable for low health literacy. Single pregnant teenagers are a special group and they should be accepted that way.